IMPLEMENTASI KEBIJAKAN PENGELOLAAN RETRIBUSI PASAR DALAM MENUNJANG PENDAPATAN ASLI DAERAH DI KABUPATEN PULAU MOROTAI (Suatu studi di Dinas Perindakop dan UMKM) - LEASIWAL, DJEIN; LALOMA, ALDEN; PALAR, NOVIE ANDERS (JURNAL ADMINISTRASI PUBLIK, 2017)
Retribution is a potential source of potential local revenue because the scope of imposition of regional retribution more widelythan the local taxes. Development of regional retribution is easier compared to local taxes since the scope of imposition ofregional retribution is not as restrictive as compared to local taxes. Therefore, local governments in order to develop localrevenues are more focused on efforts to increase the acceptance of regional retribution.This study aims to determine theimplementation of the policy on the management of levy of the market in support of local revenue in the district of MorotaiIsland.This research uses descriptive qualitative approach by describing the data obtained from the result of the research onpolicy implementation the management of leevy of the market in support of local revenue. The subject of this research is theemployees of the department of perindakop and smes and the market traders. In qualitative research data collection is done byobservation, interview, and documentation and data analysis technique consist of data reduction, data presentation andwithdrawal of conclusion/verification. Policy implementation the management of levy of the market in support of local revenuein the district of Morotai Island for the moment this is not optimal as seen from the indicators of the content of policy and theimplementation environment is still far espected as well as the lack of attention from the government especially in theimplementation of market retribution policyKeyword: Policy Implemetation, Market Levy